The Asymmetric Effects of Global Energy and Food Prices, Exchange Rate Dynamics, and Monetary Policy Conduct on Inflation in Indonesia - Arintoko, Arintoko; Badriah, Lilis Siti; Kadarwati, Nunik (Ekonomika, 2024)
This research analyzes the asymmetric effects of global energy and food prices and monetary variables, including the exchange rate and money supply, on the consumer price index (CPI). The model is intended to differentiate the influence of increases and decreases in global energy and food prices, exchange rates, and money supply which cause inflation/deflation from changes in the CPI. The analysis uses the Nonlinear Autoregressive Distributed Lag (NARDL) and Quantile Regression models on data from January 2001 to February 2023. The study results show that the decline in global energy prices significantly reduces the CPI in the long run. Energy subsidies allow increases in international energy prices not to increase the CPI significantly. Meanwhile, the increase in global food prices causes inflation in the short run. The exchange rate has the most significant effect on the CPI. Depreciation of the rupiah significantly increases the CPI, which means it causes inflation, while appreciation of the rupiah does not have a significant effect. Finally, increases and decreases in the money supply have a considerable positive effect on the CPI, which confirms the logic of the monetarist view that inflation is a monetary phenomenon. Efforts to reduce dependence on imports of food and energy commodities are the key to reducing risks when importing energy and food due to rupiah depreciation. Efforts to consistently stabilize the exchange rate can support controlling and stabilizing import prices. Energy and food subsidy policies are vital in controlling inflation due to increased world energy and food prices.